The use of maize tassel as an agricultural by-product to ameliorate heavy metals in contaminated groundwater - Dadzie, Dzifa; Quainoo, Albert K.; Obiri, Samuel (Research in Biotechnology, 2011)
The presence of heavy metals in drinking water usually tends to pose some adverse effects to the consumers. It is in the light of this that maize tassel which is usually an agricultural by product was used to remove mercury arsenic, manganese and lead from contaminated water. Maize tassel was milled into fine powder. A laboratory simulated contamination of the above mentioned metals was prepared to a concentration of 2.000Ã‚Â mg/L. Groundwater contaminated samples were also obtained and run through 20.0g of the powdered maize tassel at specific time steps of 0, 15, 30, 45 and 60 minutes respectively. The water that drained out of the tassel was then analyzed for the amount of metals remaining in it using Shimadzu Atomic Absorption Spectrophotometer model AA6300. The concentrations of arsenic, manganese lead and mercury in the laboratoryÃ‚Â simulated solution after it had passed through the maize tassel for a period of 60 minutes was 0.001 mg/L, 0.005 mg/L, 0.203 mg/L and 0.020 mg/L respectively. The concentrations of arsenic, manganese, lead and mercury in the contaminated groundwater after passing through the tasselÃ‚Â was 0.0005 mg/L, 0.0021 mg/L, 0.050 mg/L and 0.025 mg/L respectively.